Exploring the Impact of Social Media on Online Marketing Strategies in the Era of Information Technology: Challenges and Opportunities in Anticipation of the New Year - Frans Sudirjo; Chairul Anam; Iswahyu Pranawukir (Politeknik Ganesha Medan, 2023)
In the past few decades, significant business transformations have occurred alongside the development of Information Technology (IT). The paradigm shift from conventional marketing to online marketing strategies has become a necessity for companies aiming to remain relevant and competitive in an increasingly interconnected global market. This research aims to explore the impact of social media on online marketing strategies in the era of information technology as we approach the New Year. The study employs a comprehensive examination of available literature using qualitative analysis to gain a thorough understanding of the topic, covering the timeframe from 2015 to 2023. The study's findings indicate that in the ever-evolving realm of digital communication, the symbiotic relationship between social media and online marketing has become a transformative force, reshaping global business strategies. As we approach the threshold of a new year, it is crucial to conduct a comprehensive exploration of the nuanced impact that social media exerts on online marketing within the pervasive era of information technology. This journey has illuminated both challenges faced by marketers and a plethora of opportunities awaiting them in the imminent arrival of the new year.